P250 Improving E-learning environments for tomorrow's paediatricians. (June 2019) - Larkin, Elizabeth; O'Connor, Katie; McNally, Paul
Abstract : Introduction: Students presently rely on the internet both as a data source and for educational needs; therefore, medical education should embrace changes in the learning landscape in light of technological advancements [1]. The RCSI Paediatrics undergraduate programme utilises an e-learning platform to support and reinforce didactic teaching. A quality audit of RCSI's Paediatric e-learning platform was conducted 2015 to 2018. In 2015, 75% of students surveyed reported poor platform accessibility, difficulty finding the desired information, and out-dated content. Aim: To identify effective ways of utilising an e-learning platform and improve support for learning and teaching online. Methods: Students were surveyed (n=330) and stakeholder meetings (n=20) were conducted to discuss and better understand our learners and their learning needs. User reports from the e-learning platform indicated changes in users' frequency of access and duration online. Results: Feedback in 2015 showed student engagement and satisfaction were poor. To address this problem, students were surveyed and asked to identify aspects of the e-learning environment they liked and which could be improved. Effort were made to identify e-learning platform areas requiring attention. By 2018 following implementation of platform improvements, there was a 79% increase in student visits. Improvements included usability, making the e-learning platform layout and organisation more user friendly; compatibility, improving compatibility across interfaces for better access on mobile devices; diversity, creating multimedia content allowing users to select the media options that best suit their learning needs; medical educational videos, created to demonstrate how to conduct a physical exam, take patient history, and communicate and interact with patients and their parents; and self-directed learning, students take increasing responsibility for their learning [2]. Gaining independent learning skills aid students in becoming lifelong, self-directed learners [3]. Conclusion: This audit aimed to improve medical students' user experience and create a helpful e-learning environment to prepare future paediatricians. The 2018 user reports and student feedback showed greater student satisfaction and higher e-learning engagement. References: Ruiz JG, Mintzer MJ, Leipzig RM. The impact of e-learning in medical education. Academic medicine. 2006 Mar 1;81(3):207–12. Jasper MA. The potential of the professional portfolio for nursing. J Clin Nurs 1995;4:249–55. Morris, A. P., Highet, L. J, and Frazer S. E (2010) Using ePortfolios to support clinical training in paediatrics. Arch Dis Child Educ Pract Ed 2010;95:157–164. doi:10.1136/158 adc.2008.142265